The Influence of Rickettsiologists on Post-Modern Microbiology - Georgiades, Kalliopi; Merhej, Vicky; Raoult, Didier (Frontiers in Cellular and Infection Microbiology, 2011)
Many of the definitions in microbiology are factually false. We have revised the great denominations of microbiology and attempted to free microorganisms from the theories of the 20th century. The presence of compartmentation and a nucleoid in Planctomycetes clearly calls into question the accuracy of the definitions of eukaryotes and prokaryotes. Archaea are viewed as prokaryotes resembling bacteria. However, the name archaea, suggesting an archaic origin of lifestyle, is inconsistent with the actual history of this family. Viruses are defined as small, filterable infectious agents, but giant viruses challenge the size criteria used for the definition of a virus. Pathogenicity does not require the acquisition of virulence factors (except for toxins), and in many cases, gene loss seems to be implicated in the emergence of virulence. Species classification based on 16S rRNA is useless for taxonomic purposes of human pathogens, as a 2% divergence would classify all Rickettsiae within the same species and would not identify bacteria specialized for the infection of mammals. The use of metagenomics helps us to understand evolution and physiology by elucidating the structure, function and interactions of microbial communities, but it neglects the minority populations. Finally, the tree of life (TOL) theory, as established by Darwin, no longer matches our current genomic knowledge because genomics has revealed the occurrence of de novo-created genes and the mosaic structure of genomes.